Body in Consumer Culture: Postmodernism, Consumption and Body as a Commodity - Černevičiūtė, Jūratė (Problemos, 2008)
The article overviews body commodification issues in postmodern sociology discussions about identity and consumer culture. Author analyses how body images become a sign of good life and an indicator of cultural capital or as a field of hedonistic practices. There are emphasis on selfhood in contemporary consumer culture, where the body is regarded as a changeable form of existence which can be shaped according to individual needs and desires and impose the duty to care about own body as a representational object. The article analyses popular culture as a site of consumer identity implosion, fragmentation, and presents a short overview of bodily practices, which repress physical body to maintain and sustain consumerist conceptions of identity.